Additional Feeding Based on Local Food to Improve The Nutritional Status of Tooddlers (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
East Nusa Tenggara (NTT) occupies the first position in the incidence of malnutrition in Indonesia, with Kupang City as the third highest position in cases of malnutrition in NTT Province. The purpose of this study was to see the effect of supplemental feeding based on local food (Moringa nuggets) on improving status. Nutrition for toddlers. This research was conducted in 2020, using a quasi experimental research method with a pretest-posttest control group design. A total of 90 respondents were selected using purposive sampling technique. The data were collected using a questionnaire, anthropometric measurements to measure nutritional status, and recording weight gain at the beginning and end of moringa nuggets. Each research subject in the case group was given Moringa nuggets for 30 days as many as 3 pieces of nuggets per day, where each piece contained 11.4% protein. Data analysis was performed bivariately using the Pearson correlation test with α = 0.05 and pre-post comparison analysis with paired samples T-test. The results showed that there was a significant difference in changes in nutritional status of children under five before and after giving Moringa nuggets to underweight children under the anthropometric index of weight / age indicated by p = 0.041 (p 0.05). Meanwhile, the anthropometric index weight / height did not show a significant difference with a value of p = 0.052.